2010
DOI: 10.1590/s1519-69842010000100018
|View full text |Cite
|
Sign up to set email alerts
|

Lipids analysis in hemolymph of African giant Achatina fulica (Bowdich, 1822) exposed to different photoperiods

Abstract: The influence of different photophases (0, 6, 12, 18 and 24 hours) on the triglycerides and total cholesterol contents in the hemolymph of A. fulica was evaluated, since there is no information in the literature about the influence of this factor on lipids metabolism in mollusks. After 2 and 4 weeks of exposure the snails were dissected. The cholesterol content at the 2 nd and 4 th weeks post exposure only varied significantly in the groups exposed at 24 hours and 0 hour of photophase, respectively. Probably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…However, this divergent result could have been due to the use of different doses of miracidia, because Sluiters et al (1980) and Sluiters (1981) found a negative correlation between the number of eggs laid and the miracidial dose. Besides this, the influence of various environmental factors must be considered, such as food availability, photoperiod and population density (Sandland and Minchella, 2003;Gomot, 1990;Oliveira et al, 2008;Lustrino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, this divergent result could have been due to the use of different doses of miracidia, because Sluiters et al (1980) and Sluiters (1981) found a negative correlation between the number of eggs laid and the miracidial dose. Besides this, the influence of various environmental factors must be considered, such as food availability, photoperiod and population density (Sandland and Minchella, 2003;Gomot, 1990;Oliveira et al, 2008;Lustrino et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hemolymph in A. fulica also features high cholesterol levels, a result of the metabolism of lipids in these animals (Lustrino et al, 2010). This factor can also explain the preference of larvae allocation in the mantle organs, as for filling the cysts and folding the larvae, are necessary amounts of fat that possibly were easily acquired from hemolymph flowing in this region.…”
Section: Discussionmentioning
confidence: 96%
“…Changes in the metabolism of carbohydrates and protein in snails in response to parasitism, starve, population density and photoperiod were observed (LUSTRINO et al, 2010). Nevertheless, there are few studies on changes in lipid metabolism PINHEIRO, 2007).…”
Section: Determining the Concentration Of Proteins In Lipase Activitymentioning
confidence: 99%
“…In freshwater snail Lymnaea stagnalis, the photoperiod exerts an influence on the neuronal control of the cells of the lateral lobes of the cerebral ganglia (VAN MINNEN; REICHELT, 1980). But there is no information in the literature about the influence of this factor on the metabolism of lipids (triglycerides and cholesterol) of molluscs (LUSTRINO et al, 2010). Lipids have many functions in biological, energetic and structural systems (LUSTRINO et al, 2010).…”
Section: Determining the Concentration Of Proteins In Lipase Activitymentioning
confidence: 99%
See 1 more Smart Citation